2021
DOI: 10.2147/dmso.s333373
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment and Related Factors Among Middle-Aged and Elderly Patients with Type 2 Diabetes from a Bio-Psycho-Social Perspective

Abstract: This study investigated the biomedical, psychological, and social behavior risk factors for cognitive impairment in middle-aged and elderly patients with type 2 diabetes mellitus (T2DM). Methods: This cross-sectional study included 240 patients with T2DM. A questionnaire was used to collect demographic and disease-related data on patients, and the Self-rating Depression Scale (SDS), Diabetes Self-care Scale (DSCS), and Social Support Rating Scale (SSRS) were used to assess patients' depression status, self-man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…One of the biological factors that influence mental health is age. It has been discovered that older age is a risk factor for cognitive impairment, mental health, and life quality [ 28 , 29 , 30 ]. An aging body experiences involutional changes in various systems and organs, which leads to a decrease in overall efficiency, the coexistence of diseases, and changes in symptomatology [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the biological factors that influence mental health is age. It has been discovered that older age is a risk factor for cognitive impairment, mental health, and life quality [ 28 , 29 , 30 ]. An aging body experiences involutional changes in various systems and organs, which leads to a decrease in overall efficiency, the coexistence of diseases, and changes in symptomatology [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study only 17% of patients had diabetes. It is known that people with diabetes, especially with poor glycemic control, are more vulnerable to cognitive dysfunction and diabetes is associated with reduced cognitive function (Callisaya et al 2019 ; Sun et al 2020 ; Xu et al 2021 ). We indeed found that HIV-infected subjects with diabetes in our cohort had a lower MMSE score, confirming the above observations.…”
Section: Discussionmentioning
confidence: 99%
“…Our work has some strengths, to our knowledge it was one of the first studies that compares genetic polymorphisms, comorbidities, HIV-related values, and neurocognitive outcomes in HIV-infected patients. Previously, several authors studied the possible correlation between genetic polymorphisms, comorbidities or HIV-related values and neurocognitive outcomes in PWH (Foley et al 2010 ; Fogel et al 2015 ; Monroe et al, 2017; Callisaya et al 2019 ; Sun et al 2020 ; Buyo et al 2020 ; Levine et al, 2020 ; Ojeda-Juarez and Kaul, 2021 ; Xu et al 2021 ; Tahmi et al 2021 ). Notwithstanding, the combination of cognitive and physical functionality with genetic, comorbidities and HIV related values has never been assessed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Population aging is a serious social problem facing all countries in the world [1], meanwhile, the elderly in China accounted for 16.3% of the total population in 2017 and are expected to reach 492 million, or 35.2%, by 2050 [2], most of elderly have physiological function decline, malnutrition, the coexistence of a variety of chronic diseases and mental mild depression and other prominent health problems, type2 diabetes mellitus [3], cardiovascular disease [4], cognitive impairment [5] and obesity [6] are most common in elderly. Obesity is one of the most neglected health problems in the elderly, which is the accumulation of excess fat that can damage health and is a signi cant hazard to people.…”
Section: Introductionmentioning
confidence: 99%